CAMP NASIONALISME DALAM UPAYA MEMBERANTAS SIKAP RADIKALISME KALANGAN KAUM MILENIAL DI KABUPATEN BONE - A.M. Rusli; Rahmatullah Rahmatullah; Ashar Prawitno (KRITIS : Jurnal Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2022)
The notion of radicalism is still considered a serious threat to the survival of the nation and state. radicalism in Indonesia has started to increase since the last 10 years. The last ten years have confirmed that radicalism has not only appeared in government institutions, but also in community institutions, including in the field of education. During the last 10 years, the alarm for a radicalism movement in Indonesia has actually sounded. This program has been carried out on July 25-26 2021. The form of activity is in the form of outdoor and indoor activities with the camp or camp method. In addition to training independence, the choice of the camp method will also be more effective because the training participants will be maximized at the activity location and participants can experience an increase in understanding. The activity will be carried out for 3 days with training methods using a system of lecture methods, simulations, case studies, brainstorming, games, discussions and watching short films. Outcome The target for this long-term service is the birth of anti-radicalism cadres who have the awareness, soul and spirit to defend the country and are able to prevent radicalism among youth. For the Academic Targets planned for this service, it is used as a reference in making national journals/proceedings and international journals, especially relating to the attitude of love for the homeland and publications in the mass media.